What is hiding behind the money accumulating in Utah?. (November 2021) - Tenenbaum, Howard
Taking up the geographer's task of following and defetishizing the commodity, this research taps into the United States (US) federal banking data to locate the commodity "money". Law is used to specify money's locations. Relative to the size of its economy, Utah's banks report a lopsided share of US money. This paper unmasks important social relations embedded in the money commodities located in Utah's banks by tracing the history of US banking law, which has played a leading role in the processes responsible for Utah's outsized share of the sub-national monetary landscape. Banking law determined the scope and type of business in which banking firms and their corporate affiliates could engage. Throughout the 20th century, investment banks and commercial firms struggled to claim legal rights to engage in business combinations once deemed illegal: combining non-banking business with a commercial bank. The state of Utah, in coordination with financial and commercial firms, has expanded the legal and financial space of Industrial Loan Banks (ILBs), historically idiosyncratic chartered banks exempt from regulations separating banking firms from non-banking business. Utah marketed their banking charters to global, systemically important financial institutions and large commercial conglomerates, which then established or acquired ILB subsidiaries within the state. From Utah, the die had been cast: the largest non-banking firms on the planet were now legally empowered to accumulate capital in ways that had heretofore been forbidden at other locations. American banking had been transformed.